Quantitative patterns of vertical transmission of deformed wing virus in honey bees - Amiri, Esmaeil (PLoS One, 2018)
Deformed wing virus (DWV) is an important pathogen in a broad range of insects, including honey bees. Concordant with the spread of Varroa, DWV is present in the majority of honey bee colonies and can result in either low-level infections with asymptomatic bees that nonetheless exhibit increased colony loss under stress, or high-level infections with acute effects on bee health and viability. DWV can be transmitted vertically or horizontally and evidence suggests that horizontal transmission via Varroa is associated with acute symptomatic infections. Vertical transmission also occurs and is presumably important for the maintenance of DWV in honey bee populations. To further our understanding the vertical transmission of DWV through queens, we performed three experiments: we studied the quantitative effectiveness of vertical transmission, surveyed the prevalence of successful egg infection under commercial conditions, and distinguished among three possible mechanisms of transmission. We find that queen-infection level predicts the DWV titers in their eggs, although the transmission is not very efficient. Our quantitative assessment of DWV demonstrates that eggs in 1/3 of the colonies are infected with DWV and highly infected eggs are rare in newly-installed spring colonies. Additionally, our results indicate that DWV transmission occurs predominantly by virus adhering to the surface of eggs (transovum) rather than intracellularly. Our combined results suggest that the queens’ DWV vectoring capacity in practice is not as high as its theoretical potential. Thus, DWV transmission by honey bee queens is part of the DWV epidemic with relevant practical implications, which should be further studied.